(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The fact that the history and development of this problem in Uzbek literary criticism is directly related to Russian literary criticism has been proven with specific examples, it is proven that the history and development of this problem in Uzbek literary criticism is directly related to Russian literary criticism.